Financial times briefing on sustainable business - Clegg, Brian (Financial Times Prentice Hall, 2011)
This text gives executives the low-down on all the key issues in the critical area of sustainable business, helping businesses improve their strategy for sustainability so they can also provide real business benefit to their organisation.